2018
DOI: 10.1111/jmcb.12493
|View full text |Cite
|
Sign up to set email alerts
|

The Real‐Time Properties of the Bank of Canada's Staff Output Gap Estimates

Abstract: We study the revision properties of the Bank of Canada's staff output gap estimates since the mid‐1980s and show that the average revision has been significantly smaller since the early 2000s. Alternatively, revisions from econometric output gap estimates have not experienced a similar improvement. We show that the overestimation of potential output in real time following the 1991–92 recession explains the large revisions in the first half of the sample. Although Phillips‐curve inflation forecasts slightly wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
(128 reference statements)
0
18
0
1
Order By: Relevance
“…When available, we use these additional forecasts.17 SeeMacklem (2002) for details about the information and analysis presented by the staff to the Governing Council. We highlight the fact that these are staff estimates and thus may not be the same estimates provided in the MPR, the Bank of Canada publication containing detailed economic analysis and economic outlook and representing the view of the Governing Council, available every quarter since 2001.18 For example,Champagne et al (2016) use the same projections dataset to study the real-time properties of the Bank of Canada's staff output gap estimates.…”
mentioning
confidence: 99%
“…When available, we use these additional forecasts.17 SeeMacklem (2002) for details about the information and analysis presented by the staff to the Governing Council. We highlight the fact that these are staff estimates and thus may not be the same estimates provided in the MPR, the Bank of Canada publication containing detailed economic analysis and economic outlook and representing the view of the Governing Council, available every quarter since 2001.18 For example,Champagne et al (2016) use the same projections dataset to study the real-time properties of the Bank of Canada's staff output gap estimates.…”
mentioning
confidence: 99%
“…Evaluating out-of-sample inflation forecasts by means of a standard Phillips curve forecasting equation manifests the finding in the literature that no statistically meaningful distinction can be made between differently filtered gap measures (see e.g. Edge and Rudd, 2016;Champagne et al, 2018;Kamber et al, 2018). This reflects the general difficulty of beating univariate inflation forecast models with output gap based models (Atkeson and Ohanian, 2001;Fisher et al, 2002;Orphanides and van Norden, 2005;Watson, 2007, 2008), rather than output gap measurement problems.…”
Section: Introductionmentioning
confidence: 85%
“…Ever since Orphanides and van Norden (2002) have provided evidence for the poor real-time performance of commonly used output gap estimation methods, the debate regarding the reliability of output gap estimates has been vivid. 1 Recently, Edge and Rudd (2016) and Champagne et al (2018) have shown that the reliability of Federal Reserve and Bank of Canada staff output gap estimates has increased since the mid-1990s, while the reliability of purely statistical detrending procedures, like, for example, the Hodrick-Prescott (HP) filter, continues to be poor. In a recent article, Hamilton (2018b) has proposed a new regression based filter for detrending time series as an alternative to the HP filter.…”
Section: Introductionmentioning
confidence: 99%
“…Because the neutral policy rate is not Bank of Canada staff have tended to overpredict the output gap and the policy interest rate. As discussed in Champagne (2018b), the magnitude of revisions to real-time estimates of the output gap have generally fallen over time. Consistent with the results from the forecast error decompositions displayed in figure 6, Bank of Canada staff appear to have tendency to overpredict the output gap when making their forecasts, particularly over 1993-1998 and 2011-2014.…”
Section: The Output Gap and The Neutral Nominal Policy Rate In Rementioning
confidence: 99%